2021
DOI: 10.1002/glia.24129
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life thermal stress mediates long‐term alterations in hypothalamic microglia

Abstract: Stressful environmental events in early life have long-lasting consequences on later stress responses. We previously showed that heat conditioning of 3-day-old chicks during the critical period of heat-response development leads to heat vulnerability later in life. Here we assessed the role of early-life heat stress on the inflammatory response in the chick anterior hypothalamus (AH), focusing on hypothalamic microglia. We identified the microglial cell population in the chick AH using anti-KUL01 and anti-CD45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“… 31 In an early study of HS on the inflammatory response in the anterior hypothalamus (AH) of chicks, it was found that HS altered the reactivity of hypothalamic microglia as manifested by suppression of microglia in response to LPS stimulation. 57 Another important issue during the assessment of microglia status, in addition to morphological approaches, is the reliance on Iba‐1 immunoreactivity to report their activation status. 58 Interestingly, our study found a considerable increase in microglial cell overactivation and proliferation in the HS animal model, which was alleviated by BHBA therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 In an early study of HS on the inflammatory response in the anterior hypothalamus (AH) of chicks, it was found that HS altered the reactivity of hypothalamic microglia as manifested by suppression of microglia in response to LPS stimulation. 57 Another important issue during the assessment of microglia status, in addition to morphological approaches, is the reliance on Iba‐1 immunoreactivity to report their activation status. 58 Interestingly, our study found a considerable increase in microglial cell overactivation and proliferation in the HS animal model, which was alleviated by BHBA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…found that HS can induce excessive activation of microglia and astrocytes during the generation of neuroinflammation 31 . In an early study of HS on the inflammatory response in the anterior hypothalamus (AH) of chicks, it was found that HS altered the reactivity of hypothalamic microglia as manifested by suppression of microglia in response to LPS stimulation 57 . Another important issue during the assessment of microglia status, in addition to morphological approaches, is the reliance on Iba‐1 immunoreactivity to report their activation status 58 .…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, consecutive LPS treatment caused long-term changes in the microglia that months later were sufficient to alter the development of pathology in an experimental mouse model of stroke (focal cortical ischemia) and impede the subsequent development of neuropathology in a spontaneous transgenic mouse model of Alzheimer’s disease-like pathology ( Wendeln et al, 2018 ). Other studies have shown how similar systemic stimuli ( Zhou et al, 2020 ), a high-fat diet ( Vargas-Rodríguez et al, 2022 ), and early life thermal stress ( Ben-Nun et al, 2022 ) can cause long-term changes in microglial responses that can impede their responses to subsequent pro-inflammatory stimuli. The immune tolerance induced in the microglia to these repeated stimuli may be a neuroprotective response to protect the CNS from repetitive or subsequent pro-inflammatory insults ( Lajqi et al, 2020 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%